Gastrointestinal Interventional Radiology (Clinical Gastroenterology, 2018)
This volume provides a concise yet comprehensive overview of gastrointestinal interventional radiology (IR). The text reviews the extensive array of gastrointestinal IR procedures available, while illustrating the ways in which IR can help and how IR may be the only means available to treat patients. The book also focuses on common clinical issues surrounding IR procedures, including how to know which procedures are best for a patient, how to prepare patients for the procedure, and how to handle complications and decide on medications after the procedure. Written by experts in the field, Gastrointestinal Interventional Radiology is a valuable resource for clinicians and practitioners that will help improve overall patient clinical outcomes. .